Association of vitamin D receptor gene polymorphisms with rheumatoid arthritis - Noelia Marquez Pete; Cristina Perez Ramirez; Maria del Mar Maldonado Montoro; Fernando Martinez Martinez; Fernando Fernández-Llimos; Antonio Sánchez Pozo; María del Carmen Ramirez Tortosa; Alberto Jiménez Morales (Archives of Medical Science)
Introduction Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease of unknown etiology which causes progressive deterioration of the joints, leading to severe pain and functional disability. Vitamin D and its receptor (VDR) play a significant part in the onset of autoimmune diseases such as RA. The purpose of this study was to evaluate the association between VDR gene polymorphisms and risk of developing RA.